A comparative study between palonosetron and granisetron to prevent postoperative nausea and vomiting after laparoscopic cholecystectomy - Dhurjoti Prosad Bhattacharjee; Satrajit Dawn; Sushil Nayak; Pramod Ranjan Roy; Amita Acharya; Ramkrishna Dey (Wolters Kluwer Medknow Publications, 2010)
Background: Postoperative nausea and vomiting (PONV) is commonly seen after laparoscopic surgery. In this randomized double blind prospective clinical study, we investigated and compared the efficacy of palonosetron and granisetron to prevent postoperative nausea and vomiting after laparoscopic cholecystectomy. Patients & Methods: Sixty female patients (18-65 yrs of age) undergoing elective laparoscopic cholecystectomy were randomly allocated one of the two groups containing 30 patients each. Group P received palonosetron 75 μg intravenously as a bolus before induction of anaesthesia. Group G received granisetron 2.5 mg intravenously as a bolus before induction. Results: The incidence of a complete response (no PONV, no rescue medication) during 0-3 hour in the postoperative period was 86.6% with granisetron and 90% with palonosetron, the incidence during 3-24 hour postoperatively was 83.3% with granisetron and 90% with palonosetron. During 24-48 hour, the incidence was 66.6% and 90% respectively (p<0.05). The incidence of adverse effects were statistically insignificant between the groups. Conclusion: Prophylactic therapy with palonosetron is more effective than granisetron for long term prevention of postoperative nausea and vomiting after laparoscopic cholecystectomy.